Investigating the Impact of Instagram Travel Influencers on the Travel Intentions of Chinese Students Studying in the UK - Lin, Hongyu (International Journal of Global Economics and Management, 2024)
Social media influencers (SMIs) marketing has proven to be a successful strategy in the travel industry, engaging with specific consumer target groups in a trustworthy and approachable manner. Of the many social media platforms, Instagram is the most popular with Generation Y and Z. The majority of Chinese students in the UK for higher education are Gen Z and Chinese students spend the most on travel in the UK. Therefore, the aim of this study is to investigate the impact of Instagram travel influencers on the travel intentions of Chinese students studying in the UK. This study proposed hypotheses based on the Stimulus-Organism-Response model that the quality of information generated by Instagram travel influencers, their credibility and popularity & engagement have a positive effect on the generation of follower trust, and that trust has a positive effect on travel intention. To test the hypotheses, this study collected data from Chinese Gen Y and Z students studying in the UK by means of a questionnaire. The results showed that the credibility and popularity & engagement of Instagram travel influencers had a positive effect on followers generating trust and trust had a positive effect on travel intention, while the quality of information generated by Instagram travel influencers had no effect on trust. This study contributes to the existing literature for the impacts of SMIs on international students’ travel intention and provides practical implications for travel agencies in the UK to choose propriate SMIs to promote the destinations and for travel influencers to reap benefits from the travel industry.